Locoregional Control Benefit of a Tumor Bed Boost for Ductal Carcinoma In Situ - Alexandra D. Dreyfuss, MD; Danielle Max, PA; Jessica Flynn, PhD; Zhigang Zhang, PhD; Erin F. Gillespie, MD; Amy Xu, MD, PhD; John Cuaron, MD; Boris Mueller, MD; Atif J. Khan, MD; Oren Cahlon, MD; Simon N. Powell, MD, PhD; Beryl McCormick, MD; et al. (Advances in Radiation Oncology, 2023)
Purpose: Radiation therapy (RT) after breast-conserving surgery (BCS) for ductal carcinoma in situ (DCIS) reduces invasive and in situ recurrences. Whereas landmark studies suggest that a tumor bed boost improves local control for invasive breast cancer, the benefit in DCIS remains less certain. We evaluated outcomes of patients with DCIS treated with or without a boost. Methods and Materials: The study cohort comprised patients with DCIS who underwent BCS at our institution from 2004 to 2018. Clinicopathologic features, treatment parameters, and outcomes were ascertained from medical records. Patient and tumor characteristics were evaluated relative to outcomes using univariable and multivariable Cox models. Recurrence-free survival (RFS) estimates were generated using the Kaplan-Meier method. Results: We identified 1675 patients who underwent BCS for DCIS (median age, 56 years; interquartile range, 49-64 years). Boost RT was used in 1146 cases (68%) and hormone therapy in 536 (32%). At a median follow-up of 4.2 years (interquartile range, 1.4-7.0 years), we observed 61 locoregional recurrence events (56 local, 5 regional) and 21 deaths. Univariable logistic regression demonstrated that boost RT was more common among younger patients (P < .001) with positive or close margins (P < .001) and with larger tumors (P < .001) of higher grade (P = .025). The 10-year RFS rate was 88.8% among those receiving a boost and 84.3% among those without a boost (P = .3), and neither univariable nor multivariable analyses revealed an association between boost RT and locoregional recurrence. Conclusions: Among patients with DCIS who underwent BCS, use of a tumor bed boost was not associated with locoregional recurrence or RFS. Despite a preponderance of adverse features among the boost cohort, outcomes were similar to those of patients not receiving a boost, suggesting that a boost may mitigate risk of recurrence among patients with high-risk features. Ongoing studies will elucidate the extent to which a tumor bed boost influences disease control rates.